Challenges in Multimorbidity Research: Lessons Learned From the Most Recent Randomized Controlled Trials in Primary Care - Fortin, Martin; Stewart, Moira; Almirall, José; Beaupré, Priscilla (Frontiers in Medicine, 2022)
Multimorbidity has received much attention and there is a growing number of original studies. However, randomized controlled trials (RCTs) have failed to demonstrate effectiveness of interventions aimed at improving outcomes for patient with multimorbidity in primary care. The purpose of this article is to synthesize and analyze the most recent RCTs to identify the factors that may have contribute to the success or lack of success in order to draw lessons to inform further development in intervention research. A scoping review was conducted to include current up-to-date state-of-the-art studies in primary care published from 2019. Nine articles reporting on six RCTs studies were included in the review. The findings were mixed, with primary outcomes showing no differences between intervention and control groups in four of the six but differences in secondary outcomes in all six. All studies involved family practice patients but interventions took place at different sites, and the time between the beginning of the intervention and the time of evaluation of outcomes varied across studies. Authors reported issues regarding the need for training of care teams, the roles and composition of the teams, the selection of patients and implementation barriers of the complex interventions in trying contexts with not enough time for the changes required The randomized controlled design may not be the best evaluation design given the complexity of the interventions, and alternative designs should be considered in which qualitative components are included. Further attention to outcome measures and to equity issues is recommended.